Phenological of Cutleaf Groundcherry (Physalis angulata L.) Based on BBCH Scale - Anita Firdaus; Sumeru Ashari; Lulu Lazimatul Khoiriyah; Budi Waluyo (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Cutleaf groundcherry (Physalis angulata L.) is a plant that belongs to the Solanaceae family. In Indonesia, this plant grows spread in various regions and has different names in each region. However, this plant is rarely cultivated and is generally considered a weed by farmers. Recently many studies have shown that cutleaf groundcherry contains many substances that are beneficial for the health sector, so it has the potential to be developed as a cultivation plant for exotic fruit sources that function as nutraceuticals. Plant breeding programs can be a solution in responding to these problems. As the first step in developing cutleaf groundcherry through a breeding program, the Plant Breeding Laboratory, Faculty of Agriculture, Brawijaya University, collected accessions of cutleaf groundcherry from various regions in Indonesia. The phonological stage of its growth is one piece of information that is useful in better understanding the cutleaf groundcherry life cycle and, as a result, simplifying cutleaf groundcherry cultivation management. This research aims to provide practical knowledge on the cutleaf groundcherry life cycle to develop a more efficient plant management approach for cultivation, including plant breeding initiatives. The BBCH scale was used to make observations (Biologische Bundesanstalt, Bundessortenamt und CHemische Industrie). The descriptive statistics obtained from observations and presented in descriptive narrative form using the BBCH scale with 3-digit coding numbers and documentation images were used in the data analysis. The results showed that the BBCH scale was used to define and describe cutleaf groundcherry phenology, which included germination (stage 0), leaf development (stage 1), side shoot formation (stage 2), the emergence of inflorescence (stage 5), flowering (stage 6), fruit development (stage 7), fruit and seed ripening (stage 8) and senescence (stage 9)